Horrid Henry and the Abominable Snowman - Simon, Francesca; Ross, Tony (London : Orion Children's Books, 2015)
There's a snowman-building contest in town and the grand prize is a year's supply of free ice cream Horrid Henry just has to beat Moody Margaret and her dumb old ballerina snowman. So Henry makes the biggest monster snowman ever. But Henry might have to use a few last-minute tricks to win this one. Plus three other stories that won't melt.
Keywords: English - Fiction